Differential Diagnosis of Recurrent Hypersomnia: A Case Report of Primary Narcolepsy and Acute Transient Psychotic Attack - Joanna Maria Kıyak; Sezen Köse; Melek Hande Bulut Demir; Burcu Özbaran (Galenos Yayinevi, 2021)
Narcolepsy is a childhood and adolescence disorder, that until recently remained unidentified until adulthood, with a reported time from onset to diagnosis of around a decade. This disorder affects approximately 0.05% of the population and starts in childhood and adolescence about half of the time. The main symptom of hypersomnia is excessive daytime sleepiness or prolonged night-time sleep that has occurred for at least 3 months prior to diagnosis. Patients with narcolepsy also exhibit hallucinations and delusions, however the differential diagnosis between the disorders is often unclear. Case presented in our study is an example of atypical narcolepsy with coexistence of psychotic symptoms. In our case upon the set-off of the second attack of excessive daytime sleepiness, the differential diagnosis of recurrent hypersomnia was not considered. This is due to the fact that the first attack of narcolepsy with hallucinatory component of the patient could have been misdiagnosed as acute transient psychotic attack. Hallucinations and delusions sometimes appear in patients with narcolepsy. The differential diagnosis between the disorders is not always simple. In our study we present the case which illustrate this overlap. Child and adolescent patients, which demonstrate psychotic symptoms and excessive daytime sleepiness component, should be concidered in case of evaluation for a diagnosis of primary hypersomnia following a multidisciplinary cooperation of neurologists, paediatricians and psychiatrists.